2006
DOI: 10.2355/isijinternational.46.1277
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field Modeling of Structural Elongation and Alignment of (α+γ) Microstructure in Fe–0.4C Alloy during Thermomagnetic Treatment

Abstract: During last decade, the phase-field method has emerged across many fields in materials science as the powerful tool to simulate and predict the complex microstructure developments. In this study, the microstructure changes of g precipitation in polycrystalline a phase during thermomagnetic treatment in Fe-0.4C alloy are modeled using the phase-field method. Using phase-field simulation, the model reasonably represents microstructure changes in Fe-0.4C system quantitatively. In particular, it is shown that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…The effects of a magnetic field on carbon diffusivity have been reported by Nakamichi et al [45] and Ohtsuka and Hao [46] and they both found that carbon diffusivity is retarded by a magnetic field, but they did not find any anisotropy of diffusivity. Koyama and Onodera [47] have modeled the structural change and carbon distribution for the lath martensite to austenite transformation in a magnetic field using the phase-field method. They found that the carbon distribution is affected by a magnetic field and results in the formation of an elongated structure.…”
Section: Effects Of a Magnetic Field On Transformed Structure For γ →mentioning
confidence: 99%
“…The effects of a magnetic field on carbon diffusivity have been reported by Nakamichi et al [45] and Ohtsuka and Hao [46] and they both found that carbon diffusivity is retarded by a magnetic field, but they did not find any anisotropy of diffusivity. Koyama and Onodera [47] have modeled the structural change and carbon distribution for the lath martensite to austenite transformation in a magnetic field using the phase-field method. They found that the carbon distribution is affected by a magnetic field and results in the formation of an elongated structure.…”
Section: Effects Of a Magnetic Field On Transformed Structure For γ →mentioning
confidence: 99%
“…Since the magnetic energy E d suppresses phase decomposition along the direction of magnetic moment, composition modulation along the direction of external magnetic field does not progress [57]. [69]. The microstructure change in the upper row demonstrates the temporal evolution of the phase field that represents the polycrystalline grain structure, where the gray and white regions indicate the α ferrite phase and γ austenite phase, respectively.…”
Section: Microstructure Design In Fe-cr-co Spinodal Magnetmentioning
confidence: 99%
“…The following simulation is an attempt at modeling this complex microstructure change by the phasefield method. Figure 5 shows the two-dimensional simulation of phase transformation and microstructure development in Fe-0.4 mass%C at 1023K with an external magnetic field along the vertical direction [69]. The sequence of phase transformation and microstructure changes with isothermal aging is represented in figures 5(a)-(d).…”
Section: Microstructure Change In Fe-c Steel Under External Magnetic mentioning
confidence: 99%
“…The coupled simulations have been performed in several real magnetic material systems, for example, Ni 2 MnGa ferromagnetic shape memory alloys [30], FePt nanogranular thin films [31], Co-Sm-Cu rare-earth magnets [32], Fe-Cr-Co alloys [33], and Fe-C steels [34]. In the above studies, the micromagnetic approach was used directly under the assumption of ''strongenough'' external magnetic field.…”
Section: Introductionmentioning
confidence: 99%